WORKING STUDENT’S PERSPECTIVES ON THE FLIPPED CLASSROOM APPROACH FOR ENHANCING READING SKILL - Adi, Adi; Yahmun, Yahmun; Suhartatik, Suhartatik (The Ellite of Unira, 2025)
This research studies working students' perspectives on the flipped classroom model as a strategy to enhance their reading skills. Using qualitative research methods, semi structured interviews are conducted with 20 working students balancing work and studies. The findings show that 75% of participants perceive the flipped classroom approach as significantly improving their reading skills by allowing them to prepare theirself before class. However, 25% of the participants show that its effectiveness depends on the quality of materials given. These findings highlight the importance of designing high quality of material to maximize the benefits of flipped classrooms for diverse learners. Future research can explore ways to optimize flipped classroom materials for students woith limited time. For addition, educators need to address technological and accessibility challenges to ensure inclusivity.